Marketing management : With Cases - Kotler, Philip; Keller, Kevin Lane (New Delhi : Pearson, 2016)
Business
Keywords: Marketing Management; Marketing Method; Developing marketing strategies and plans; Marketing memo; Marketing research; Customer value; Consumer market; Product strategy; Delivering value; Communicating value